2019
DOI: 10.1108/ijpsm-05-2019-0131
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management processes and performance

Abstract: Purpose The purpose of this paper is to investigate the impact of ownership of public sector organizations on the implementation of knowledge management (KM) processes and subsequent performance. Design/methodology/approach Using 268 responses obtained from a structured country-wide survey, the study assesses the hypothesized differences in the implementation of KM processes (knowledge creation, knowledge capture and storage, knowledge sharing and knowledge application and use), the overall performance benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 58 publications
(49 reference statements)
0
15
0
1
Order By: Relevance
“…For example, KM processes improved municipal efficiency (Mohajan, 2017; Dikotla, 2016; Gaffoor and Cloete, 2010) in South Africa. Elsewhere in the world, though operational performance, The Malaysian Agricultural Research and Development Institute improved productivity by using technology to capture and share farming expertise and knowledge (Balasubramanian et al , 2019). Moreover, operational performance emanating from KM programmes enabled the Korean Customs Service to achieve savings of KRW500m by developing a recycling programme for counterfeit shoes (Asian Productivity Organisation report [APO], 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, KM processes improved municipal efficiency (Mohajan, 2017; Dikotla, 2016; Gaffoor and Cloete, 2010) in South Africa. Elsewhere in the world, though operational performance, The Malaysian Agricultural Research and Development Institute improved productivity by using technology to capture and share farming expertise and knowledge (Balasubramanian et al , 2019). Moreover, operational performance emanating from KM programmes enabled the Korean Customs Service to achieve savings of KRW500m by developing a recycling programme for counterfeit shoes (Asian Productivity Organisation report [APO], 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, operational performance emanating from KM programmes enabled the Korean Customs Service to achieve savings of KRW500m by developing a recycling programme for counterfeit shoes (Asian Productivity Organisation report [APO], 2013). To benefit from these three types of performance aspects offered by KM programmes, public sector organisations need to devise and operationalise performance measures to monitor their KM performance on a continuous basis (Balasubramanian et al , 2019) to assess the effectiveness of KM practices and determine if the current knowledge process manage knowledge effectively and efficiently. Wang and Zheng (2010) advise that KM performance evaluation should include the criteria for designing evaluating and selecting the methods of evaluating KM performance.…”
Section: Discussionmentioning
confidence: 99%
“…Path analysis (testing hypotheses 2, 3, and 4). To test our hypotheses regarding the relationships (hypotheses 2, 3, and 4), path analysis and multigroup analysis using IBM AMOS 25 were performed to estimate the differences in the relationships (Balasubramanian et al, 2019) across the leaders and followers, as hypothesized. However, before proceeding with the tests, it was important to ensure that significant differences existed in the overall model for leaders and followers.…”
Section: Model Fit Sem Using Ibm Amos 25 Software Was Employed To Check the Model Fit Of The Structural Modelmentioning
confidence: 99%
“…[4], [16], [13], and [17], [19] supported that intellectual capital has positive and significant influence on firm performance. [8], [13], [18], and [20] have found that knowledge management has influence positively to firm performance. [6] and [3] mentioned that intellectual capital plays a role as an input for knowledge management.…”
Section: Framework and Hypothesismentioning
confidence: 99%